Integrating Computer Self-Efficacy into the Technology Acceptance Model in the Case of Millennial Users of Lazada - Prilya Angel Putri (iBuss Management, 2019)
Indonesia is the fastest growing e-commerce market in the world, giving huge opportunity as it is still in the early process of adapting e-commerce. Hence, it is important for Lazada to take advantage of the growing e-commerce market and maintain its position as the biggest e-commerce website in Indonesia. In order to do so, Lazada needs to understand the perception of these e-commerce users and its influence on behavioral intention to use. Therefore, this research aims to analyze the effect of computer self-efficacy and Technology Acceptance Model (TAM) on the user’s behavioral intention to use Lazada.This research is conducted by distributing questionnaire to 200 respondents, age of 19 to 36 and have ever used Lazada. The sampling method used is the simple random sampling method. The data then was analyzed with Structural Equation Modeling. The findings validate that (1) computer self-efficacy has a significant impact to perceived ease of use and perceived usefulness of the technology, (2) perceived ease of use and perceived usefulness have a significant impact to attitude towards using technology, and (3) attitude towards using the technology has a significant impact to behavioral intention to use technology. Keyword:Computer Self-Efficacy, Technology Acceptance Model, Behavioral Intention to Use, E-Commerce, Lazada